Distinctive Deep‐Level Defects in Non‐Stoichiometric Sb2Se3 Photovoltaic Materials - Weitao Lian; Rui Cao; Gang Li; Huiling Cai; Zhiyuan Cai; Rongfeng Tang; Changfei Zhu; Shangfeng Yang; Tao Chen (Advanced Science, 2022)
Abstract Characterizing defect levels and identifying the compositional elements in semiconducting materials are important research subject for understanding the mechanism of photogenerated carrier recombination and reducing energy loss during solar energy conversion. Here it shows that deep‐level defect in antimony triselenide (Sb2Se3) is sensitively dependent on the stoichiometry. For the first time it experimentally observes the formation of amphoteric SbSe defect in Sb‐rich Sb2Se3. This amphoteric defect possesses equivalent capability of trapping electron and hole, which plays critical role in charge recombination and device performance. In comparative investigation, it also uncovers the reason why Se‐rich Sb2Se3 is able to deliver high device performance from the defect formation perspective. This study demonstrates the crucial defect types in Sb2Se3 and provides a guidance toward the fabrication of efficient Sb2Se3 photovoltaic device and relevant optoelectronic devices.